Non-Marginal Cost-Benefit Analysis and the Tyranny of Discounting - Koen Vermeylen (Tinbergen Institute, 2013)
This paper uses the Kaldor-Hicks compensation principle to compute the present value (PV) of a non-marginal future event. Three theoretical results stand out: First, decreasing returns to capital create a wedge between the PV of future generations' willingness to pay (WTP) and the PV of their willingness to accept compensation (WTA); second, the discount rates implicit in the computation of the PVs are endogenous, and rising (declining) over time for the future generations' WTP (WTA); and third, decreasing returns to capital may make it impossible to compensate future generations according to their WTA, effectively defeating the tyranny of discounting. A back-of-the-envelope calibration suggests that this last result is realistic in the case of climate change. A cost-benefit analysis based on the Kaldor-Hicks compensation principle may therefore be impossible if futu re generations are entitled to a world without climate change; and an environmental trust fund - no matter how large it is - may be insufficient to adequately compensate future generations.
Keywords: D61; E13; H43; Q51; Q54; 330; climate change; cost-benefit analysis; discounting; WTP; WTA